Enhanced Solar Photocatalytic Activity of Thermally Stable I:ZnO/Glass Beads for Reduction of Cr(VI) in Tannery Effluent - Ashar, Ambreen; Bhatti, Ijaz Ahmad; Mohsin, Muhammad; Yousaf, Maryam; Aziz, Humera; Gul, Adeeba; Hussain, Tausif; Bhutta, Zeeshan Ahmad (Frontiers in Chemistry, 2022)
Chromium (VI) in tannery effluent is one of the major environmental concerns for the environmentalists due to the hazardous nature of Cr(VI) ions. To reduce Cr(VI) to Cr(III) as an innocuous moiety, pure and I-doped ZnO was grafted over the etched surface of glass beads by successive ionic layer adsorption and reaction (SILAR). Powdered, pure, and I-doped ZnO scrapped from the surface of glass beads was characterized for crystallinity, morphology, and elemental composition by XRD, SEM, TEM, and EDX. The optical properties of both photocatalysts revealed that owing to optimized iodine doping of ZnO, reduction in the bandgap was observed from 3.3 to 2.9 eV. The crystalline nano-bricks of I:ZnO adhered to glass beads were investigated to have remarkable capability to harvest sunlight in comparison to intrinsic ZnO nanodiscs. The thermal stability of I:ZnO was also found to be much improved due to doping of ZnO. The photocatalytic activities of ZnO/GB and I:ZnO/GB were compared by extent of reduction of Cr(VI) under direct natural sunlight (600–650 KWh/m2). The disappearance of absorbance peaks associated with Cr(VI) after treatment with I:ZnO/GB confirmed higher photocatalytic activity of I:ZnO/GB. The reaction parameters of solar photocatalytic reduction, i.e., initial pH (5–9), initial concentration of Cr(VI) (10–50 ppm), and solar irradiation time (1–5 h) were optimized using response surface methodology. The solar photocatalytic reduction of Cr(VI) to Cr(III) present in real tannery effluent was examined to be 87 and 98%, respectively, by employing ZnO/GB and I:ZnO/GB as solar photocatalysts. The extent of reduction was also confirmed by complexation of Cr(VI) and Cr(III) present in treated and untreated tannery waste with 1, 5-diphenylcarbazide. The results of AAS and UV/vis spectroscopy for the decrease in concentration of Cr also supported the evidence of higher efficiency of I:ZnO/GB for reduction of Cr(VI) in tannery effluent. Reusability of the fabricated photocatalyst was assessed for eight cycles, and magnificent extent of reduction of Cr(VI) indicated its high efficiency. Conclusively, I:ZnO/GB is a potential and cost-effective candidate for Cr(VI) reduction in tannery effluent under natural sunlight.